RESPONSE of TOW POTATO CULTIVARS TO HUMIC ACID FERTILIZER - Fathel Ibraheem (Mesopotamia Journal of Agriculture)
This study was carried out at vegetables field of Horticulture and landscape department, College of Agriculture and Forestry, Mosul University, Iraq., during spring season 2013, to investigate the effect of Humic Acid addition in three concentrations (0, 3 and 4 g/l), adding of Humic Acid was in three stages: first at full germination, second 20 days after first stage while third stage was 20 days after second stage in vegetative growth and yield characters of tow potato cultivars (Universa and Alaska). The obtained results could be summarized as follows: Universa cultivar showed a significant increase in fresh weight, dry weight and plant leaf area as compared Alaska cultivar. Humic Acid at 3gm/l leads to a significant increase all vegetative growth and yield characters with a significant decrease of non-marketable yield as compared to control plants and most of the treatment at 4 gm/l, whereas using of Humic Acid at 4 gm/l concentration leads to a significant increase in dry weight and leaf area/plant as compared to control plants with significant increase in dry weight/plant treated with 3 gm/l of Humic Acid as compared with the same treatment at 4 gm/l. The interaction between Universa cultivar and Humic Acid at 3 gm/l showed highest values in all study characters except stems number, tuber number and non-marketable yield as compared to other treatments.